ANALYSIS OF SUPREME COURT DECISION NO. 1271 K/Pdt/2009 CONCERNING BREACH OF PERFORMANCE IN INTERNATIONAL BUSINESS CONTRACTS - Rouli Anita Velentina; Cahya Utami Aldana (Catalist Indo Publisher, 2026)
Cross-border business agreements pose significant challenges in Private International Law (PIL), particularly in defining and resolving cases of default (breach of contract). This study deeply examines the Indonesian Supreme Court Verdict Number 1271 K/Pdt/2009, which adjudicated a payment default dispute for ship repair services between PT LI (a domestic entity) and TSC (a foreign entity), to identify the implications of establishing default, jurisdiction, and compensation. Employing a normative juridical method and a case study approach, the analysis focuses on interpreting the principles of the Law of Obligations within the Indonesian Civil Code (KUH Perdata) as applied to a transnational context. The research findings affirm the rejection of the appeal (cassation) and the reinforcement of the Judex Facti's (lower court judges') verdict, confirming that the foreign party was legally proven to be in default. While this decision establishes legal certainty for the domestic creditor, the case critically underscores the complexity in determining relative authority (jurisdiction) within domestic courts, as well as the inconsistency in the judicial consideration of the awarded compensation amount. Consequently, it is concluded that optimal legal protection in international contracts relies heavily on explicit choice of law and dispute resolution clauses, where Alternative Dispute Resolution (ADR) often offers higher efficiency compared to prolonged litigation pathways.